A review of transparent-reflective switchable glass technologies for building facades. (December 2021) - Tong, Shi Wun; Goh, Wei Peng; Huang, Xiaohu; Jiang, Changyun
Abstract: Transparent-reflective switchable (TRS) glass is an emerging technology that provides active control of solar radiation. Efficient TRS glasses have advantages over other smart windows, such as traditional electrochromic glasses, for radiant energy control because they modulate the sunlight transmission based on light reflection, which prevents unnecessary indoor heating by sunlight through the fenestrations. The high translucence tunability not only allows the optimization of indoor temperature, it also provides glare control for building occupants' visual comfort. There are several aspects, however, that require further improvements to accelerate the commercialization of TRS glasses. This review aims to validate four state-of-the-art TRS glass technologies as ideal energy-efficient building glazing, by comparing their key optical switch response, challenges and potential solutions. With further technical revolutions being made in new materials, device configuration and low-cost manufacturing processes, TRS glasses are touted to be essential elements in climate-adaptive building envelopes. Graphical abstract: Image 1 Highlights: Solar radiation management using transparent-reflective switchable (TRS) glass. Modulating light reflection/transmission of TRS glass under electrical stimulus. Smart windows as essential energy-saving elements in building envelopes. Four TRS glasses based on different working mechanisms are critically reviewed.